Evolution and Advancement of Adult Spinal Deformity Research and Clinical Care: An Overview of the Scoli-RISK-1 Study. Issue 1 (May 2019) - Cerpa, Meghan; Lenke, Lawrence G.; Fehlings, Michael G.; Shaffrey, Christopher I.; Cheung, Kenneth M. C.; Carreon, Leah Yacat
Study Design: Narrative review. Objective: The prevalence of adult spinal deformity (ASD) has been cited anywhere between 2-32%, while the prevalence in the elderly population has been estimated at 68%. Neurologic complications following ASD surgery remains a concern. Previous literature reported incidence of neurologic complications varied between 1-10%, while non-neurologic complications reported were as high as 50%. To assess the incidence of neurologic deficits, complications, and outcomes following ASD surgery, an international group of spine deformity surgeons initiated a prospective, multicenter, international, observational study: Scoli-RISK-1. Methods: Two hundred seventy-two patients were enrolled from 15 centers with ASD having primary or revision surgery with a major Cobb≥80°, revision including an osteotomy, and/or a complex 3-column osteotomy. Patients had lower extremity muscle strength (LEMS) exams performed preoperatively and at specific time points through 2-year follow-up. Results: Preoperatively, 203 patients (74.9%) had no LEMS impairment (normal) and 68 (25.1%) had a LEMS of <50 (abnormal). Compared with baseline, 23.0% of all patients experienced a LEMS decline at discharge, with this rate decreasing to 17.1% at 6-weeks and to 9.9% at 6-months and remaining stable at 10.0% at 2-years. Conclusion: This study revealed that a decline in LEMS after complex ASD surgery is common and more frequent than previously reported. We identified such a decline in 23.0% of patients at discharge, with neurologic function recovering over time to a decline of 10.0% at 2-years postoperatively. The Scoli-RISK-1 study revealed valuable information regarding the incidence, natural history, and prognosis of neurologic and non-neurologic complications following ASD surgery and provides useful information for patient counseling.